2014
DOI: 10.1039/c4ta04070h
|View full text |Cite
|
Sign up to set email alerts
|

Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT

Abstract: In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C-and Sibridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…As such, the V oc of these devices are generally smaller than the V oc of counterpart solar cells comprising only the parent donor-acceptor pair. [ 13,14,18,[23][24][25][26] With a series of papers, Thompson and co-workers [ 11,12,19,[27][28][29][30] demonstrated that the V oc of ternary-blend solar cells need not be pinned by the smallest energy level difference of the constituents, as described above. In fact, with proper selection of materials combination for ternary-blend active layers, the V oc of these solar cells can be continuously tuned with composition between those derived from the HOMO energy levels of the individual donors.…”
mentioning
confidence: 99%
“…As such, the V oc of these devices are generally smaller than the V oc of counterpart solar cells comprising only the parent donor-acceptor pair. [ 13,14,18,[23][24][25][26] With a series of papers, Thompson and co-workers [ 11,12,19,[27][28][29][30] demonstrated that the V oc of ternary-blend solar cells need not be pinned by the smallest energy level difference of the constituents, as described above. In fact, with proper selection of materials combination for ternary-blend active layers, the V oc of these solar cells can be continuously tuned with composition between those derived from the HOMO energy levels of the individual donors.…”
mentioning
confidence: 99%
“…This approach has been intensively studied and is also feasible in tandem devices. [29][30][31][32] The module costs of the upscaling and the industrial scenario are dependent on further parameters, especially the electrode costs. Since these costs are especially addressed in the upscaling and industrial model no module costs are mentioned for these scenarios in Table 2.…”
Section: Cost Analysis For Single and Tandem Modules -State Of The Armentioning
confidence: 99%
“…3,4,[19][20][21][22][23]24 However, simultaneous increase in the Voc, Jsc and FF is a challenge in the ternary approach because of the trade-off between photocurrent and voltage. 23,25,26 Reports show ternary blends using fullerene acceptors, where the Voc is increased using a second acceptor (A2) with a higher electron affinity (EA) than A1; 23,27-29 however, very few examples of two-acceptor ternary blend devices could surpass the overall efficiency of their respective binary blends.…”
Section: Introductionmentioning
confidence: 99%